Apoptotic cells enhance pathogenesis of Listeria monocytogenes. (April 2017) - Pattabiraman, Goutham; Palasiewicz, Karol; Visvabharathy, Lavanya; Freitag, Nancy E.; Ucker, David S.
Abstract: Infections by pathogenic microorganisms elicit host immune responses, which crucially limit those infections. Pathogens employ various strategies to evade host immunity. We have identified the exploitation of the repertoire of potent immunosuppressive responses elicited normally by apoptotic cells ("Innate Apoptotic Immunity"; IAI) as one of these strategies. In the case of Listeria monocytogenes, an environmentally ubiquitous, foodborne bacterial pathogen capable of causing life-threatening invasive disease in immunocompromised and elderly individuals, the induction of host cell apoptosis appears to play an important role in pathogenesis. Previous studies have documented extensive lymphocyte apoptosis resulting from L. monocytogenes infection and demonstrated paradoxically that lymphocyte-deficient animals exhibit diminished susceptibility to listerial pathogenicity. We speculated that the triggering of IAI following the induction of host cell apoptosis was responsible for enhanced pathogenesis, and that the administration of exogenous apoptotic cells would serve to exert this effect. Importantly, apoptotic cells, which are not susceptible to L. monocytogenes infection, do not provide a niche for bacterial replication. Our experiments confirm that apoptotic cells, including exogenous apoptotic cells induced to die independently of the pathogen, specifically enhance pathogenesis. The recognition of a role of apoptotic cells and Innate Apoptotic Immunity in microbial pathogenesis provides an intriguing and novel insight for therapeutic approaches for the control of pathogenic infections. Graphical abstract: Apoptotic lymphocytes, generated in a pathogen-dependent manner contingent upon Listeriolysin O (LLO), trigger innate apoptotic immune (IAI) responses, which enhance L. monocytogenes pathogenesis. The effect of IAI is particularly apparent in an inflammatory context. Macrophages (and other cell types), in the presence of L. monocytogenes, are stimulated (via [Toll-like and other] innate immune receptors) to release pro-inflammatory cytokines and chemokines, which enhance anti-pathogen responses by altering vascular permeability and expanding, recruiting, and activating immune effector cells. (This is the case for uninfected as well as infected macrophages.) In the presence of apoptotic cells, however, pro-inflammatory cytokine expression is repressed and anti-inflammatory cytokine expression is induced. Our experiments demonstrate that apoptotic lymphocytes, generated independently of the pathogen, enhance pathogenesis as well. In lymphocyte-deficient animals, the infusion of exogenous apoptotic cells reconstitutes this process of enhanced pathogenesis. Highlights: Apoptotic cells enhance the pathogenicity of Listeria monocytogenes . The pathogenesis-enhancing effect is a property of apoptotic cells generally, independentof mode of apoptosis induction. Enhancement of microbial pathogenesis is a property unique to apoptotic cells and not othertypes of dead cells. Apoptotic enhancement of microbial pathogenesis is evident in the absence of adaptive immune function. We speculate that enhancement of pathogenesis reflects apoptotic immunomodulatoryeffects ("Innate Apoptotic Immunity").